In vivo preliminary evaluation of the analgesic activity of the flowers of Brugmansia arborea “floripondium” - Valle Hernández, Clara Marian; Moreno Mendoza, Miguel Ángel; Linares Rivera, Abraham Ernesto; Mendoza Portillo, Evelyn Virginia; Mejía-Valencia, José Guillermo (Revista Minerva, 2023)
Objective: To investigate the analgesic effect of the decoction of the flowers of Brugmansia arborea "floripondium" in laboratory mice. Methodology: To determine the analgesic activity, 9 albino mice (males) of the NIH strain were used, between 5 weeks of age and a body weight between approximately 21 - 24.5 g, all from the Animal Experimentation Laboratory of the Center for Research and Development in Health of the University of El Salvador. For the preparation of the decoction, 5 g of fresh plant material (flowers) were placed in 50 ml of water until it boiled. Then the decoction of the flowers of Brugmansia arborea was administered orally at a concentration of 0.1g/mL. The mice were divided into three groups; a negative control group (distilled water), a positive control group (Ibuprofen 200 mg/kg) and the treatment group (decoction of floripondium flowers). One hour after the substances were administered, 1% acetic acid was injected intraperitoneally. After five minutes, the number of abdominal contortions in each animal was counted. Results: The groups administered with Ibuprofen and the treatment obtained an average of 11.33 and 15.67 respectively, considerably reducing the number of abdominal contortions, compared to the group treated with distilled water, which obtained an average of 34.67. Conclusions: The decoction of the flowers of Brugmansia arborea in the acetic acid test showed that it has a potential analgesic effect in laboratory mice.